2016
DOI: 10.18632/oncotarget.13582
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine/spermine N1-acetyltransferase regulates cell growth and metastasisviaAKT/β-catenin signaling pathways in hepatocellular and colorectal carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) and colorectal cancer (CRC) are among the most common cancers across the world. Therefore, identifying the potential molecular mechanisms that promote HCC and CRC progression and metastasis are urgently needed. Spermidine/spermine N1-acetyltransferase (SSAT) is a catabolic enzyme that acetylates the high-order polyamines spermine and spermidine, thus decreasing the cellular content of polyamines. Several publications have suggested that depletion of intracellular polyamines inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 61 publications
3
50
0
Order By: Relevance
“…Polyamine depletion has been suggested for cancer prevention, but α-difluorometh ylornithine (DFMO) was not clinically effective neither alone nor in combination with other agents (28). Depletion of polyamines by spermidine/spermine N1-acetyltransferase (SSAT) significantly inhibited cellular proliferation, migration, and invasion through the AKT/GSK3β/β-catenin signaling pathway in hepatocellular carcinoma and colorectal cancer cells (29). However, previous studies reported that inhibition of spermidine production promoted colorectal cancer growth (15), and that exogenous spermidine suppressed hepatocellular carcinomas in mice (16).…”
Section: Discussionmentioning
confidence: 99%
“…Polyamine depletion has been suggested for cancer prevention, but α-difluorometh ylornithine (DFMO) was not clinically effective neither alone nor in combination with other agents (28). Depletion of polyamines by spermidine/spermine N1-acetyltransferase (SSAT) significantly inhibited cellular proliferation, migration, and invasion through the AKT/GSK3β/β-catenin signaling pathway in hepatocellular carcinoma and colorectal cancer cells (29). However, previous studies reported that inhibition of spermidine production promoted colorectal cancer growth (15), and that exogenous spermidine suppressed hepatocellular carcinomas in mice (16).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the polyamines spermine (Spm) and spermidine (Spd) are often naturally present in food [8]. However, also their excess has been recently associated with potential health risks [9,10]. Despite their recognized toxicity, the limit concentrations of BAs in fermented foodstuffs are far from being adequately standardized by regulatory agencies.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study, we found that DKK3 restoration decreases p-GSK3β and nuclear β-catenin expression in adult B-ALL. A recent study showed that spermidine/spermine N1-acetyltransferase (SSAT) overexpression inhibits β-catenin nuclear translocation and decreases p-GSK3β expression through AKT activation [ 37 ]. The Pseudomonas aeruginosa mannose-sensitive hemagglutinin (PA-MSHA) was reported to reduce β-catenin and p-GSK3β by affecting the PTEN/AKT signaling pathway [ 38 ].…”
Section: Discussionmentioning
confidence: 99%